Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic) - Biscoito, Manuel; Saldanha, Luiz (Zootaxa, 2018)
Gaidropsarus mauli, new species, is described from the Lucky Strike Hydrothermal vent site (Mid-Atlantic Ridge) and from the Bay of Biscay. It is distinguished from congeners by a combination of characters such as the number of vertebrae, the size of the first dorsal-fin ray, the profile of the head and the shape of the snout, in dorsal view, the size and the position of the eyes, the length of the pelvic fins, the shape of the pectoral fins, and the length of the lateral line. A comparison with the other 13 valid species of the genus is presented.